Conceptualising the management of packaging within new product development. Issue 11 (4th November 2014) - Simms, Christopher; Trott, Paul
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this study is to: contribute to existing models of new product development (NPD) and provide new understanding of how a new product's packaging is managed and integrated into the NPD process of fast-moving consumer goods (FMCG) firms and build on prior research, suggesting that firms lack a pipeline of new packaging innovations by uncovering the factors that influence this pipeline issue. Design/methodology/approach – A grounded theory methodology was adopted. Research was conducted through a total of 37 interviews with key informants in the UK FMCG industry, packaging industry and associated firms. Findings – Three distinct levels of packaging development were revealed: skin deep, body modification and format change. The emphasis within many firms is primarily on changes to packaging at the level of the label (skin deep) or aesthetic design (body modification), whilst technological and format changes are overlooked. The factors that contribute to the level at which development is undertaken are identified. Research limitations/implications – Existing literature has largely examined packaging at the level of skin-deep and body modification. The development of new packaging technology has been overlooked. This study's propositions guide the way forward for further research. Practical implications – For firms, the development of new formats and genuine packaging innovation may be being overlooked. There is a need for them to re-examine their activities to ensure that they are addressing all three levels. Originality/value – This theory-building study has generated a new typology which, alongside the unique framework, reveals the factors influencing the level of emphasis within firms.